Thymosin α 1 potentiates the release by CD8+ cells of soluble factors able to inhibit HIV-1 and human T lymphotropic virus 1 infection in vitro. (July 2015) - Matteucci, Claudia; Minutolo, Antonella; Pollicita, Michela; Balestrieri, Emanuela; Grelli, Sandro; D'Ettorre, Gabriella; Vullo, Vincenzo; Bucci, Ilaria; Luchini, Alessandra; Aquaro, Stefano; Sinibaldi-Vallebona, Paola; Macchi, Beatrice; et al.
<x xml:space="preserve">Abstract</x> Background: Thymosin α-1 (Tα1) exploits a specific action on lymphoid cells and is able to induce in peripheral blood mononuclear cells (PBMCs) a strong transcriptional response. CD8 antiviral factor activity plays a role in the control or prevention of HIV-1 infection by a non-cytolytic mechanism. The ability of Tα1 to modulate the release of antiretroviral soluble factors by CD8+ cells was investigated. Methods: Supernatants from lipopolysaccharide (LPS) stimulated CD8+-isolated cells treated with Tα1 were screened on in vitro infection of human monocyte-derived macrophages (MDMs) and PBMCs with HIV-1, and of PBMCs with human T lymphotropic virus 1 (HTLV-1). In CD8+ cells, as well as in PBMCs of healthy donors as from HIV+ individuals, a microarray analysis to assess the transcriptional response after treatment was performed. Results: Tα1 potentiates the release, in LPS-stimulated CD8+ cells, of soluble factors able to inhibit both in vitro HIV-1 infection of MDMs and PBMCs and in vitro HTLV-1 infection of PBMCs. A distinctive transcriptional profile was induced by Tα1 in PBMCs from HIV+ donors. Conclusions: These findings suggest that Tα1 would represent a re-evaluated approach to antiretroviral therapy in combination with innovative treatments and with vaccine administration.